One-Year Follow-up of Children and Adolescents with Major Depressive Disorder: Relationship between Clinical Variables and Abcb1 Gene Polymorphisms - Blázquez, A.; Gassó, P.; Mas, S.; Plana, M. T.; Lafuente, A.; Lázaro, L. (Pharmacopsychiatry, 2016)
Introduction: Differences in response to fluoxetine (FLX) may be influenced by certain genes that are involved in FLX transportation (ABCB1). We examined remission and recovery from the index episode in a cohort of patients treated with FLX, and also investigated associations between genetic variants in ABCB1 and remission, recovery, and suicide risk.Methods: This was a naturalistic 1-year follow-up study of 46 adolescents diagnosed with major depressive disorder (MDD). At 12 months they underwent a diagnostic interview with the K-SADS-PL.Results: It was found that remission was around 69.5% and recovery 56.5%. Remission and recovery were associated with lower scores on the CDI at baseline, with fewer readmissions and suicide attempts, and with lower scores on the CGI and higher scores on the GAF scale. No relationship was found between ABCB1 and remission or recovery. However, a significant association was observed between the G2677T ABCB1 polymorphism and suicide attempts.Conclusion: Other factors such as stressful events, family support, and other genetic factors are likely to be involved in MDD outcome.
Keywords: fluoxetine; recovery; remission; suicide attempts; ABCB1